Technostress in Post-Pandemic Higher Education: Prevalence and Coping Mechanisms - Banu, Smrithi (Journal of Educational Research and Policies, 2025)
This study explored the Technostress among College Students in The New Normal during the school year 2020-2021. Eleven participants were the selected BSED students who experienced online delivery of instruction. A case study was utilized based on the interpretivist paradigm. The study intended to know the forms, causes, effects on academic performance, and coping strategies of technostress. Multiple data sources were collected, such as the TSC Questionnaire that measured the level of students' technostress and Interview Guide Questions answered by participants. To triangulate participants' responses, four subject teachers were also interviewed. Findings notably identify two forms of technostress experienced by the participants, such as emotional discomfort and body pains caused by various challenges of distance learning. Alongside these forms of technostress are remarkable coping strategies that somehow help students manage various discomforts and difficulties as means of survival. As part of the implication, the participants' coping strategies were composed of three stages: acknowledging the technostress, evaluating coping skills, and mitigating the technostress by applying available resources. Based on the findings, an implication for managing technostress was then provided.